Diary of a wimpy kid : the ugly truth - Kinney, Jeff. (New York : Amulet Books, 2010)
While trying to find a new best friend after feuding with Rowley, middle-school slacker Greg Heffley is warned by older family members that adolescence is a time to act more responsibly and to think seriously about his future.
Keywords: Maturation (Psychology) -- Fiction; Family life -- Fiction; Humorous stories